Long‐term acceleration of aseismic slip preceding the Mw 9 Tohoku‐oki earthquake: Constraints from repeating earthquakes. Issue 22 (19th November 2015) - Mavrommatis, Andreas P.; Segall, Paul; Uchida, Naoki; Johnson, Kaj M.
Abstract: A decadal‐scale deformation transient preceding the 2011 M w 9 Tohoku‐oki, Japan, earthquake was reported from continuous GPS data and interpreted as accelerating aseismic slip on the Japan Trench megathrust. Given the unprecedented nature of this transient, independent confirmation of accelerating slip is required. Here we show that changes in the recurrence intervals of repeating earthquakes on the Japan Trench megathrust in the period 1996 to 2011 are consistent with accelerating slip preceding the Tohoku‐oki earthquake. All sequences of repeating earthquakes with statistically significant trends in recurrence interval (at 95% confidence) offshore south central Tohoku occurred at an accelerating rate. Furthermore, estimates of the magnitude of slip acceleration from repeating earthquakes are consistent with the completely independent geodetic estimates. From a joint inversion of the GPS and seismicity data, we infer that a substantial portion of the megathrust experienced accelerating slip, partly surrounding the eventual rupture zone of the M w 9 earthquake. Key Points: Independent confirmation of long‐term transient slip event preceding the M w 9 Tohoku‐oki earthquake Repeating earthquakes during 1996–2011 occurred at an accelerated rate near the M w 9 source area Consistent estimates of slip acceleration are inferred from independent geodetic and seismicity data